Efficacy and safety of novel GZ667161 glucosylceramide synthase inhibitor to modulate CNS glucocerebrosidase activity and synucleinopathies in pre-clinical and clinical studies investigating Parkinson’s disease: a systematic review - Grigor, Emma; Montroy, Joshua; Lalu, Manoj; Mestre, Tiago; Schlossmacher, Michael; Fergusson, Dean (Université d'Ottawa | University of Ottawa, 2019)
Background: Parkinson’s disease (PD) is a disorder caused by neurodegeneration of select neuronal clusters in the central nervous system (CNS), which leads to a progressive movement disorder and associated cognitive decline over the ensuing decades. Glucosylceramide synthase (GCS) inhibitors are an exciting new treatment option for patients with PD. Here, we provide a first review that may help to inform the design of future in vivo pre-clinical trials using the CGS inhibitor, GZ667161. Methods: A comprehensive search strategy was developed with the help of an information specialist to identify studies of GZ667161 in animals or humans with parkinson's disease. Article screening, data extraction, and risk of bias assessment was done in duplicate by two independent reviewers. Results: The systematic search of the literature yielded 4 citations for possible inclusion. Following de-duplication and screening, a total of one pre-clinical study was determined to meet our full eligibility criteria for inclusion. There were no clinical studies of GZ667161 identified. The one included study saw significant reductions in glucoceramide levels in GZ667161 mice compared to controls (p<0.01). Adverse events were not reported. Conclusions: The review of the study suggests that GZ667161 may be able to reduce the levels of GlcCer in the CNS of mouse models for Parkinson disease. However, these results should be interpreted with caution, as only one study was included in the review, and it was found to be at a high risk of bias across multiple domains.
Keywords: Parkinson's; GCS inhibitor